Case series of severe neurologic sequelae of Ebola Virus Disease during epidemic, Sierra Leone. - Howlett,PJ; Walder,AR; Lisk,DR; Fitzgerald,F; Sevalie,S; Lado,M; N'jai,A; Brown,CS; Sahr,F; Sesay,F; Read,JM; Steptoe,PJ; et al. (Emerging Infectious Diseases, 2018)
We describe a case series of 35 Ebola virus disease (EVD) survivors during the epidemic in West Africa who had neurologic and accompanying psychiatric sequelae. Survivors meeting neurologic criteria were invited from a cohort of 361 EVD survivors to attend a preliminary clinic. Those whose severe neurologic features were documented in the preliminary clinic were referred for specialist neurologic evaluation, ophthalmologic examination, and psychiatric assessment. Of 35 survivors with neurologic sequelae, 13 had migraine headache, 2 stroke, 2 peripheral sensory neuropathy, and 2 peripheral nerve lesions. Of brain computed tomography scans of 17 patients, 3 showed cerebral and/or cerebellar atrophy and 2 confirmed strokes. Sixteen patients required mental health followup; psychiatric disorders were diagnosed in 5. The 10 patients who experienced greatest disability had co-existing physical and mental health conditions. EVD survivors may have ongoing central and peripheral nervous system disorders, including previously unrecognized migraine headaches and stroke.